Surgeon agreement at the time of handover, a prospective cohort study. Issue 1 (December 2016) - Hilsden, Richard; Moffat, Bradley; Knowles, Sarah; Parry, Neil; Leslie, Ken
Abstract Background Acute Care Surgical Teams are responsible for emergent surgical patients, and as such require regular handover and coordination between different surgeons. Despite the recent emergence of this model of care, minimal research has been conducted on the quality of patient handover and no research has attempted to determine the rate of clinical agreement or disagreement among surgeons participating in these teams. Methods A prospective cohort study was carried out with our acute care surgical service at a tertiary care teaching hospital from January 2 to March 31 2012. At the conclusion of the daily morning handover, receiving surgeons were asked to indicate, on provided handover sheets, whether they agreed with the proposed management plan for each patient that was discussed. The specific aspects of care over which they disagreed were also described, and disagreements were classified a priori as major or minor. The primary outcome was the rate of disagreement over the handed over management plan. Results Six staff surgeons agreed to participate and a total of 417 unique patients were handed over during the study period. For the primary outcome, a total of 41 disagreements were recorded for a disagreement rate of 9.8 %. 15 of the 41 disagreements were classified as major, for a major disagreement rate of 3.6 %. Consultant to consultant disagreements were classified as major disagreements 63 % of the time, whereas consultant to resident disagreements were classified as major 31 % of the time (P  = 0.217). On average, the age of patients for which a clinical disagreement occurred were older; 63 vs. 57 (P  < 0.05). Conclusions Despite the frequency of handovers in clinical practice, little research has been conducted to determine the rate of disagreement over patient management among surgeons participating working in academic centers. This study demonstrated that the rate of clinical disagreement is low among surgeons working in an tertiary care teaching hospital.